Percutaneous Transhepatic Gallbladder Drainage for Acute Cholecystitis During Chemotherapy: Case Series - Yoshitomi, Munehiro; Kawahara, Ryuichi; Kanno, Hiroki; Fukutomi, Shogo; Arai, Shoichiro; Goto, Yuichi; Akashi, Masanori; Sato, Toshihiro; Sakai, Hisamune; Hisaka, Toru (Brazilian Journal of Case Reports, 2025)
Clinicians may have trouble treating acute cholecystitis in patients undergoing chemotherapy. This study aimed to review the feasibility of continuing chemotherapy while a biliary tube is in place and report our experience. We retrospectively examined the records of 17 patients who underwent percutaneous transhepatic gallbladder drainage (PTGBD) for acute cholecystitis. The cohort comprised nine cases of gastrointestinal cancer and eight other malignancies. Overall, chemotherapy was resumed in 12 cases after PTGBD. These patients were divided into three groups based on the circumstances under which chemotherapy was resumed. Chemotherapy was performed with the drain in place in seven patients (14.33±6.94 days until the start of chemotherapy after drainage, group A), after cholecystectomy in three (84±56 days, group B), and after removing the drainage tube (56 days, group C) in two patients. Early administration of chemotherapy was only possible in group A. At times, clinicians are required to make complicated judgments regarding acute cholecystitis treatment that cannot be done by relying on guidelines alone. With strict control, chemotherapy can be safely resumed, even with a drainage tube in place, and PTGBD can be carefully considered for these patients. These groups were determined retrospectively based on the course of treatment.